2021
DOI: 10.3390/ijerph18073448
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic Strength, Vertical Jump Performance, and Strength Differences in First Line Professional Firefighters Competing in Fire Sport

Abstract: The purpose of our study was to investigate peak torque (PT) of knee extensors (KE) and knee flexors (KF), bilateral and unilateral strength asymmetries in isokinetic testing and vertical jump height (JH), vertical ground reaction force (VGRF), and force differences (ΔVGRF) between legs during different jump tests in professional first-line firefighters (n = 15) competing in fire sports disciplines. There was a significant effect of jump type on JH (F2,44 = 7.23, p < 0.05), VGRF (F2,44 = 16.03, p < 0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(49 reference statements)
1
0
0
1
Order By: Relevance
“…When landing, Dempsey et al (2014) found peak landing ground reaction forces were increased by up to 19% with the addition of the duty belts and loads. These findings by Dempsey et al (2014) and Wiley et al (2020) are comparable to a study within a firefighter population which found increases in vertical ground reaction forces and decreases in squat and countermovement jump height using force plate data (Miratsky et al, 2021) findings also identified in military populations (Birrell et al, 2007;Kinoshita, 1985;Lloyd & Cooke, 2000). These biomechanical alterations can lead to cumulative stresses which increases the risk of musculoskeletal injury (Birrell & Haslam, 2008;Knapik et al, 1992;Orr et al, 2021;Park et al, 2008;Polcyn et al, 2001) notably to the lower limbs (Lyons et al, 2021).…”
Section: Discussionsupporting
confidence: 66%
“…When landing, Dempsey et al (2014) found peak landing ground reaction forces were increased by up to 19% with the addition of the duty belts and loads. These findings by Dempsey et al (2014) and Wiley et al (2020) are comparable to a study within a firefighter population which found increases in vertical ground reaction forces and decreases in squat and countermovement jump height using force plate data (Miratsky et al, 2021) findings also identified in military populations (Birrell et al, 2007;Kinoshita, 1985;Lloyd & Cooke, 2000). These biomechanical alterations can lead to cumulative stresses which increases the risk of musculoskeletal injury (Birrell & Haslam, 2008;Knapik et al, 1992;Orr et al, 2021;Park et al, 2008;Polcyn et al, 2001) notably to the lower limbs (Lyons et al, 2021).…”
Section: Discussionsupporting
confidence: 66%
“…Si bien no existieron diferencias significativas entre los dos grupos de edad de los bomberos, durante la realización de las pruebas de salto vertical se observó una menor altura alcanzada durante el CMJ en comparación a los datos registrados por Lara Sánchez et al (2013), en 33 bomberos profesionales. En la misma línea, los estudios de Antolini et al (2015) y Miratsky et al (2021), en donde se evaluaron bomberos profesionales utilizando el salto vertical como parámetro de rendimiento, se mostraron valores superiores a los encontrados en este estudio. Sin embargo, la falta de diferencias encontradas en este estudio con relación a las pruebas de salto vertical, prueba de resistencia en carrera y estimación del VO2 entre los grupos de edad, coinciden con lo expuesto por Lara Sánchez et al (2013).…”
Section: Discussionunclassified